Дослідження ефективності роботи системи охолодження при інтенсифікації відтискання технічних олій в гвинтових прес-екструдерах для виготовлення паливних брикетів - Самойчук, Кирило Олегович; Самохвал, Віталій Анатолійович; Червоткіна, Олександра Олександрівна; Samoichuk, Kyryl; Samokhval, Vitalii; Chervotkina, Oleksandra (Запоріжжя : 2023, 2023)
UA: Актуальність дослідження направлена на подолання проблеми з перегріванням шнекового пресового обладнання та сировини при виготовлені паливних брикетів з оліємістких сировин з відтисканням надмірного вмісту технічних олій, яке в свою чергу в значній мірі, впливає як на якість самих технічних олій так і на якість брикету. З даною проблемою стикаються власники шнекового пресового обладнання особливо в літній період, коли температура навколишнього середовища досить висока. Дане дослідження спрямовано на подолання проблеми перегріву найбільш високотемпературних частин обладнання, на визначення оптимальних температур при виготовлені паливних брикетів на гвинтових прес – екструдерах та розробці системи охолодження пресів. Головною метою роботи є підвищення якості готової продукції за рахунок контролю температури та зниження собівартості готової продукції. Найбільш дієвими для вирішення даної проблеми є емпіричні методи дослідження. Проведено аналіз методів усунення проблеми перегріву камери дожиму та пристрою остаточного формування брикету. При розробці та реалізації ефективних засобів реалізації належного охолодження, проаналізовано конструкції відомого пресового обладнання даного типу, та обґрунтовано необхідність розроблення нового пресового обладнання в якому камера дожиму та частина секцій пристрою остаточного формування обладнана системою контролю температури. EN: The relevance of the study is aimed at overcoming the problem of overheating of screw press equipment and raw materials in the manufacture of fuel briquettes from oil-containing raw materials with the squeezing out of excessive content of industrial oils, which in turn significantly affects both the quality of the industrial oils themselves and the quality of the briquette. This problem is faced by owners of screw press equipment especially in summer, when the ambient temperature is quite high. This study aims to overcome the problem of overheating of the most heated parts of the equipment and to determine the optimal temperatures for the production of fuel briquettes using screw press extruders and the development of a cooling system. The main goal of the work is to improve the quality of finished products by controlling the temperature and reducing the cost of finished products. Empirical methods of research are the most effective for solving this problem. The paper analyzes methods for eliminating the problem of overheating of the squeezing chamber and the final briquette formation device. When developing and implementing methods for solving this problem, the designs of well-known press equipment of this type were analyzed, and the need to develop new press equipment in which the press chamber and part of the sections of the final forming device are equipped with a temperature control system was substantiated. Each of the sections of the final molding device should be equipped with a system of regulated selection of industrial oils, with the ability to interchange sections. Since when forming a briquette from oil-containing raw materials, the time spent in the press plays an important role, increasing which allows for better compression of the raw material to be formed into a briquette and separation of a larger percentage of industrial oils, the new device should increase the time spent in the compressed state. The developed equipment is mainly intended for regions where such crops as sunflower, flax, rapeseed, soybean are grown in large volumes. This equipment ensures stable operation and high quality of finished products regardless of the ambient temperature and provides an opportunity to obtain additional profit from the sale of technical oils.
Studying the efficiency of the cooling system during the intensification of extrusion of industrial oils in screw press extruders for the manufacture of fuel briquettes
Keywords: паливний брикет; прес; пресування; температурні параметри; дожимний пристрій; вихід олії; production of briquettes; press; temperature parameters; pressing device; oil output